Antibiofilm and Quorum Sensing Inhibition (QSI) Potential of Leaves Extract - Farzana Zafar; Muhammad Shahid; Hina Fatima; Muhammad Riaz; Fozia Anjum; Zahid Mushtaq; Saadiya Zia; Muhammad Muzammil Jahangir; Muhammad Amir Aslam (SAGE Publishing, 2022)
Disruption of quorum sensing pathway of pathogenic microbes is considered as novel approach to fight against infectious diseases. The current study was planned to evaluate the antibiofilm and quorum sensing inhibitory potential of Lagerstroemia speciosa . Antibacterial and antibiofilm potential of L. speciosa extracts was determined through agar well diffusion and crystal violet assay against sinusitis isolates, that is, Staphylococcus aureus, Enterococcus faecalis, Proteus mirabilis, and Klebsiella pneumoniae , while quorum sensing inhibition efficacy of L. speciosa extracts was determined through violacein inhibition assay using Chromobacterium pseudoviolaceum as bacterial model . The methanolic extract of L. speciosa presented the highest antimicrobial activity against E. faecalis and antibiofilm activity against K. pneumoniae (77.42 ± 1.51%) , while n -hexane extract was found to be least active against all tested bacterial strains . Quorum sensing inhibition activity of L. speciosa extracts against C. pseudoviolaceum showed significant dose-dependent inhibition in violacein production by different concentrations of methanolic extract. Furthermore, none of the extracts of L. speciosa showed any hemolytic activity against human RBCs and hold considerable thrombolytic potential in comparison to streptokinase (75.9 ± .46%). In conclusion, findings suggest that L. speciosa leaves are excellent source of phytochemicals with potent antibiofilm and quorum sensing inhibition potential.